Techno-economic analysis of a power-to-hydrogen system in heavy industries with and without national incentives - Ismail Marouani; Saleh Albadran; Mansoor Alturki; Yasser Almalaq; Badr M. Alshammari; Tawfik Guesmi (PLoS ONE, 2026)
This study analyzes how national incentive programs can play a transformative role in facilitating green hydrogen adoption across emission-intensive industrial sectors. Despite the recognized potential of green hydrogen for industry decarbonization, its widespread uptake remains constrained by elevated costs, limited supporting infrastructure, and technological limitations. By evaluating system optimization strategies, including PV-Wind, PEM electrolyser, energy storage and hydrogen tank sizing, this research demonstrates that targeted incentives applied to the redevelopment of legacy industrial zones can substantially reduce the Levelized Cost of Hydrogen (LCOH) from 7.8 USD/kg in baseline scenarios to 4.5 USD/kg with incentives considered, while simultaneously achieving notable reductions in greenhouse gas (GHG) emissions from approximately 3.2 kgCO₂eq/kgH₂ to near 1.4 kgCO₂eq/kgH₂. The novelty of this work is fourfold. It presents the first techno-economic optimization of Power-to-Hydrogen (PtH) systems that explicitly quantifies the interaction between national incentive schemes (0–70% CAPEX subsidies) and optimal sizing of PV, wind, electrolyzer, and hydrogen storage for heavy industrial applications. It demonstrates a linear relationship between total capital investment and LCOH (R² > 0.96), enabling rapid cost estimation without full simulations. It identifies a critical threshold for battery storage cost reduction (≥50%) before batteries become economically viable in PtH systems without incentives. It also provides a comparative analysis of incentive effects versus projected equipment cost reductions (2030–2050), showing that incentives alone can achieve 43–54% LCOH reductions. In addition, this formulated control strategy aims to accomplish three main objectives such as satisfying hourly hydrogen demand, maximizing renewable electricity utilization, and minimizing grid electricity withdrawal. The economic effect of these incentives closely rivals anticipated declines in equipment expenses projected for the coming decade. Furthermore, the observed linear relationship between capital investment and LCOH enables precise cost modelling and streamlines decision-making for site-specific implementations, minimizing the need for additional simulations.